Reclaiming their Voice : New Perspectives From Young Women and Men in Upper Egypt - World Bank (Washington, DC, 2012)
This study examines the demographic, socioeconomic, and cultural circumstances of young men and young women (aged 15-29) in Upper Egypt. Where appropriate, comparison is made with the rest of the country. It explores the perceptions of young men and women regarding the challenges and opportunities they face as they attempt to gain access to education, employment, services, and civic engagement. More broadly, the study explores their views on the factors that facilitate or limit their inclusion in the society and economy of Upper Egypt. This report focuses on two main transitions of young Upper Egyptians: the transition from school to work, and the transition to active citizenship and civic engagement. The study also briefly considers young people's engagement in the January 25th Revolution and their aspirations for the future in its aftermath. It concludes by offering recommendations for youth-inclusive policies that could expand the scope of employment and participation opportunities currently available to young people. The focus of the study being on Upper Egypt, it does not examine comprehensively the implications of youth employment and participation for Egyptian society as a whole. In its analysis of gender, the study analyses the dimension of access to education, but does not attempt to explore the issue of gender segregation in educational specialization. The report is consists of five chapters. Chapter two focuses on the transition from school to work, examining educational attainment, labor force participation, unemployment, joblessness, and gender issues. It also briefly considers youth entrepreneurship and involvement in agriculture. Civic engagement is the focus of chapter three, which presents young people's understanding of civic engagement and constraints to community participation. Chapter four considers young people's involvement in the January 25th Revolution. Conclusions and policy recommendations reflecting young people's aspirations for the future are discussed in chapter five.